INCIDENCIA DE LOS FACTORES AFECTIVOS EN LA ELECCIÓN DE ESTRATEGIAS DE APRENDIZAJE Y USO DE UNA L2 - Lorenzo, Francisco J. (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Affective factors have more often than not been given passing attention when describing the process of second language acquisition. This paper points out that however relevant cognition can be, learners also experience an affective involvement when learning a language. Empirical research has repeatedly turned its attention to affect to account for variation in second language learning but this connection takes place in a theoretical vacuum. This paper aims at presenting a framework that links affect to one of the most undisputed cognitive mechanisms in second language acquisition, that of strategies. Once this framework has been dealt with, this paper emphasizes the central role that affect should have in second language research.